L'âge du Fer en Basse-Normandie. Gestes funéraires en Gaule au Second-Âge du Fer. Volumes I et II - Barral, Philippe; Dedet, Bernard; Delrieu, Fabien; Giraud, Pierre; Le Goff, Isabelle; Marion, Stéphane; Villard-Le Tiec, Anne (Annales littéraires, 2011)
This is the publication of the proceedings of the 33rd AFEAF symposium held in Caen from the 20th to the 24th of May 2009. Like the symposium, this book is divided in two parts. The first part, with its 17 contributions, deals with the current knowledge about the Iron Age in Lower Normandy. An important renewal of the documentation concerning this region allows a better understanding of the occupational processes and territorial organization existing throughout Protohistory. This first part also includes several summary reports on rural settlements, fortified sites as well as finds. The second part of the book, with 22 contributions, deals with the subject of death and funerary practices during the 5th to 1st centuries BC. The subject was discussed focussing on a chosen number of thoughts as to make it easier to compare between different regions. Various summary reports allow an overview of this specialized topic throughout Gaul with perspectives from other regions of Celtic Europe.